Fuel savings and cost reduction of start-stop technology for an internal combustion engine / Noor Zafirah Abu Bakar - Noor Zafirah , Abu Bakar (2013)
Global warming effects have forced the regulation on carbon dioxide (CO2) emissions by vehicle to be tighter. European Union (EU) has set by 2015 the amount of CO2 emitted must be below 130 g CO2/km. Several technologies have been emerged to improve vehicle fuel efficiency which subsequently reducing the amount of CO2 emission for instance engine downsizing, hybridization and alternative fuels for instance bio-fuel, fuel cell and hydrogen. Even though these technologies have been proven capable of improving fuel efficiency, the cost incurred to develop the technologies is very high and require longer payback period. Thus, Stop-Start (SS) technology has been seen as a promising solution due to its lower development cost, less complexity architecture, shorter payback period and capable to reduce fuel consumption. The basic principle of start-stop operation is the vehicle’s control system will switch the engine off when the vehicle is idling for example in a congested traffic condition or stop at traffic light. The engine is automatically switched on when the driver presses the clutch or accelerator pedal. Start-stop system can be a standalone system and directly applied to standard conventional vehicle. This thesis presents the test methodologies and results for fuel consumption comparison between standard Persona and Persona equipped with start-stop system by using Proton Test Standard. Three different time settings were added for engine stop to evaluate the thermal cabin comfort. The data from the fuel consumption test was used to calculate the annual fuel and cost savings. The annual fuel saving computed is 296 liter/100 km and the annual cost saving is RM562.40 with the assumption that the price of fuel is RM1.90/liter. However, during the test, the battery performance showed some deterioration. Thus, it was recommended battery with higher performance needs to be used for start-stop application. For thermal comfort, the passengers were not happy with the condition during engine stop where the air-conditioner was off. Therefore, additional device such as storage evaporator is required to ensure the thermal comfort inside the cabin. This thesis also presents literature reviews on main components required when startstop technology is integrated with conventional vehicle system. The components are enhanced battery, intelligent battery sensor, integrated starter-alternator and DC to DC converter. The control strategies for engine stop and start are covered in the thesis. The advantages and challenges of this technology are also presented.